International bank for reconstruction and development, 1946 - 1953 (Baltimore, 1954)
This study of the Inter national Bank for Reconstruction and Development, 1946 1953, has been prepared by the staff of the Bank. It consists of three parts. Part I is devoted to a discussion of the purposes, organization and financial structure of the Bank. Part II sets forth the major operational policies of the Bank and describes the general character of its operations. Part III is a country-by-country summary of Bank activities. In addition, the study includes appendices containing, among other information, the Bank's Articles of Agreement and its financial statements as of December 31, 1953.
Keywords: Economics